Antecedents That Influence the Intention to Use the Uber Mobile Application: Customer Perspectives in South Africa - Maziriri, Eugine Tafadzwa; Mapuranga, Miston; Mushwana, Justice; Madinga, Nkosivile Welcome (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In today’s postmodern era, there is phenomenal growth in the use of smartphones, GPS as well as Internet. This has given a rise to a revolution in the business world and the revolution is focused on conducting business on the move usually by mobile commerce applications. The study sought to determine the impact of perceived convenience, facilitation conditions, social influence and price value on the intention to the use an Uber application. A quantitative methodology was utilised and the research concentrated specifically on consumers, located in the Johannesburg area and using of a non-probability convenience sample. A self-administered questionnaire was designed based on the scales used in previous studies. The statistical data analysis procedures utilised for the quantitative study were descriptive statistics, correlation analysis, reliability analysis, structural equation modelling approach by means of the partial least squares structural equation modelling approach. The hypotheses testing results revealed that the intention to use an Uber application was influenced significantly and positively by perceived convenience, facilitation conditions, social influence and price value. The study authenticates those factors such as perceived convenience, facilitating conditions, social influence and price value are instrumental in stimulating the intention to use the Uber application. Lastly, based on the findings of this study, limitations were discussed along with the recommendations and concluding remarks.